Cryptoblabes gnidiella Millière (Pyralidae, Phycitinae): An Emerging Grapevine Pest in Greece - Konstantinos B. Simoglou; Iraklis Topalidis; Dimitrios N. Avtzis; Achilleas Kaltsidis; Emmanouil Roditakis (Insects)
The honeydew moth, Cryptoblabes gnidiella Millière (Lepidoptera: Pyralidae), is native to the Mediterranean Basin. However, it has recently been reported as an emerging grapevine pest in southern European Union countries and in the Middle East, North Africa, and South America. This may be attributed to the global warming trends. In this brief communication, we present the first documented cases of honeydew moth infestation of grapevine in Greece, specifically in two organic vineyards in the Regional Unit of Drama in Northeastern Greece in 2024. Notably, the infestations were limited to the late-ripening grape cultivar ‘Xinomavro’, harvested in October, while other cultivars such as ‘Assyrtiko’, ‘Malagousia’, ‘Cabernet sauvignon’, ‘Sauvignon blanc’, ‘Limniona’, ‘Chardonnay’, and ‘Agiorgitiko’, harvested in late August and early September, showed no signs of infestation. This suggests that the actual impact of C. gnidiella in Greece may be underestimated, as previous late summer infestations of lepidopteran larvae in vineyards were likely misattributed to L. botrana. We discuss the potential implications and concerns regarding the occurrence and management of this pest in Greece.